2021
DOI: 10.3390/healthcare9060765
|View full text |Cite
|
Sign up to set email alerts
|

Interpretative Phenomenological Analysis for the Comparison of Polish and Foreign Dentistry Students’ Concerns during the Covid-19 Pandemic

Abstract: Introduction: At the beginning of 2020, the worldwide infection of coronavirus (SARS-CoV-2) changed many aspects of human lives. The controlled lockdown was not only an obligatory lifestyle change to communities across the globe, but it was also an emotional struggle. The aim of the presented study was to identify and compare the main difficulties that final-year students (both Polish and foreigners) of Dentistry, Faculty of Medical Sciences in Zabrze Medical University of Silesia had to cope with during the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Moreover, Shepherd et al [ 22 ] found that the majority of students confirmed that their mental health had deteriorated as a result of the COVID-19 restrictions, expressing anxiety, panic, stress and fear. In another study conducted in Poland, it was reported that students were exposed to a significant number of stressful situations during the COVID-19 pandemic such as disruptions in academic sessions, diminished social and family interactions, particularly for foreign-language students who remained in the place where they stay away from their families and homes [ 23 ]. During the first phase of the UK lockdown (April-June 2020), a convenience sample of 168 school-aged children aged 7.6–11.6 years in the UK found a significant increase in depression symptoms compared to the initial assessment 18 months prior to the lockdown [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Shepherd et al [ 22 ] found that the majority of students confirmed that their mental health had deteriorated as a result of the COVID-19 restrictions, expressing anxiety, panic, stress and fear. In another study conducted in Poland, it was reported that students were exposed to a significant number of stressful situations during the COVID-19 pandemic such as disruptions in academic sessions, diminished social and family interactions, particularly for foreign-language students who remained in the place where they stay away from their families and homes [ 23 ]. During the first phase of the UK lockdown (April-June 2020), a convenience sample of 168 school-aged children aged 7.6–11.6 years in the UK found a significant increase in depression symptoms compared to the initial assessment 18 months prior to the lockdown [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted in many centres have shown that the lack of clinical classes was a strong stressor for dental students [ 4 , 6 , 9 , 48 , 50 ]. As a consequence, anxiety about their future professional careers arose [ 7 ]. At this point, it is worth emphasising, once again, that the education of dental students is practical in nature.…”
Section: Discussionmentioning
confidence: 99%
“…For dentistry students, this meant theoretical classes held online and pre-clinical activities using medical patient simulators, as well as clinical classes with real patients. These were situations which could have potentially enabled infection [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation